Meningkatkan Kepuasan Kerja: Peran Work Life Balance dalam Memediasi Fleksibilitas dan Budaya Kerja - wilyningsih, ni ketut ayu; Yuliana, Ika; Makiah, Makiah; Febriana, Widia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
PT Gojek Indonesia Tbk is a prominent Indonesian technology firm renowned for its diverse digital services, including transportation, food delivery, retail, and payment solutions. PT Gojek employs a workforce division, which includes Gojek drivers. The quality of work outcomes is contingent upon the job happiness of Gojek drivers. Work flexibility and organisational culture directly impact job satisfaction, while indirectly, they may be influenced by work-life balance. The study comprised 84 samples obtained through purposive sampling. The findings indicated that work flexibility did not significantly impact job satisfaction. The work culture exerted a favourable and substantial influence on job satisfaction. Work flexibility exerted a favourable and substantial influence on work-life balance. The work culture did not significantly impact work-life balance. The equilibrium between work and personal life exerted a favourable and substantial influence on job satisfaction. Work-life balance can facilitate the connection between work flexibility and job happiness. WLB cannot facilitate the connection between work culture and job happiness.